2011
DOI: 10.1111/j.2044-8279.2011.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Assessment for Learning Questionnaires for teachers and students

Abstract: The TAFL-Q and SAFL-Q capture the construct AFL in two subscales: Monitoring and Scaffolding, and allows for comparisons between teacher and student perceptions. The instruments can be useful tools for teachers and students alike to identify and scrutinize assessment practices in classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 26 publications
1
61
0
3
Order By: Relevance
“…In defining the construct of AfL, common principles in most studies are identified as: (1) rich classroom questioning, (2) facilitating self-and peer assessments, (3) clarifying goals and criteria and (4) giving feedback/feedforward (Assessment Reform Group, 2002;Black & Wiliam, 1998a;James & Pedder, 2006;Whitelock, 2010). As suggested by Stiggins (2005) and Pat-El, Tillema, Segers, and Vedder (2013), these four general principles can be further subsumed under two functions of AfL: (a) monitoring to track student progress and (b) scaffolding to show students or help students recognise what areas need improvement. Monitoring refers to analysing student learning progress to foster student self-monitoring with the intent to find challenges and opportunities for optimising learning.…”
Section: Incongruent Perceptions Of Assessment For Learning Practicementioning
confidence: 98%
See 1 more Smart Citation
“…In defining the construct of AfL, common principles in most studies are identified as: (1) rich classroom questioning, (2) facilitating self-and peer assessments, (3) clarifying goals and criteria and (4) giving feedback/feedforward (Assessment Reform Group, 2002;Black & Wiliam, 1998a;James & Pedder, 2006;Whitelock, 2010). As suggested by Stiggins (2005) and Pat-El, Tillema, Segers, and Vedder (2013), these four general principles can be further subsumed under two functions of AfL: (a) monitoring to track student progress and (b) scaffolding to show students or help students recognise what areas need improvement. Monitoring refers to analysing student learning progress to foster student self-monitoring with the intent to find challenges and opportunities for optimising learning.…”
Section: Incongruent Perceptions Of Assessment For Learning Practicementioning
confidence: 98%
“…Perceptions of AfL practices were measured with the Assessment for Learning questionnaire which consists of both a teacher and a student version (Pat-El et al, 2013). This questionnaire was validated to compare teacher and student perceptions of classroom AfL practice.…”
Section: Dependent Variable Perception Of Aflmentioning
confidence: 99%
“…The extent to which AfL was embedded in classrooms was measured with the Student Assessment for Learning Questionnaire (SAFL) (Pat-El et al, 2013). Students completed the two scales that measure students' perceptions of monitoring (16 items, a = .89) and scaffolding (12 items, a = .83).…”
Section: Methodsmentioning
confidence: 99%
“…This study builds on the construct validity of questionnaires by Pat-El et al (2013) and Vandevelde et al (2013). As these measures have not been used in the context of Dutch elementary education before, the construct validity of the questionnaires was assessed in the present sample with separate confirmatory factor analyses (CFA) for each questionnaire.…”
Section: Measurement Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation